Particulate matter inside residences of elderly in the Metropolitan Area of São Paulo - Segalin, Bruna (2017)
The elderly population is sensitive to damages caused by air pollution on health. They spend relatively more time indoors, however there is limited information on the air quality they breathe inside their residences. The objectives of this work are to characterise mass of sizesegregated particulate matter (PM) in elderly residences in Metropolitan Area of Sao Paulo (MASP) in Brazil; assess the meteorological parameters influence; evaluate the indoor and outdoor relationship of PM; quantify the ions, trace elements and black carbon (rBC) in quasi-ultrafine particles (qUFP) and identify their sources, and estimate the respiratory deposition doses (RDD). To achieve these objectives, we measured during 24 hours the mass concentrations of PM in differents sizes (102.5, 2.51.0, 1.00.5, 0.50.25 and <0.25 µm (PM0.25, qUFP) in 59 elderly residences in MASP using a Personal Cascade Impactor Sampler. The PM10 is the sum of all size and PM2.5 is PM10 less PM102.5. The PM2.5 and PM0.25 contributed 78% and 38% of total PM10, respectively. About 77% and 40% of the residences had higher PM2.5 and PM10 than those in outdoor environments. About 13 and 43% of the measurements exceeded the World Health Organization (WHO) guidelines for PM10 and PM2.5, respectively. The PM0.25 exceeded the WHO guideline for PM2.5 in 8.3% of residences. Residences with higher PM concentration in all size bins are predominantly near the heavy traffic areas during the nonprecipitation days. About 68% of residences have the highest mass concentration in PM0.25. We analysed ions by chromatography, trace elements by x-ray fluorescence and rBC by reflectance. The major of ions concentrations in qUFP were found to be SO42- and NH4+, and the major trace elements were Si and Fe. Around 26% of the qUFP is rBC. Some residences have a high concentration of the toxic heavy metals Cu, Ni, Pb and Cr. We identified 6 dominant sources of the indoor qUFP by positive matrix factorization: vehicular emission (57%), secondary inorganic aerosol (21%), soil and construction (7%), wall painting (7%), cooking (5%) and industry (3%). The RDD for coarse and fine particles were found to be 20% and 24.6% higher for male than female elderly during seated position, respectively. The maximum RDD of qUFP and rBC are in the tracheobronchial part. It is important the control of PM sources in the elderly residences to limit adverse health effects of PM, especially fine particles. We suggest consider the rBC as one regulated air pollutant in terms of public control actions for air quality improvement in MASP.